Histopathological evaluation of tumours and tumour like lesions of skin and adnexa - Karki, Diksha; Jha, Abhimanyu; Shreevastav, Shreya; Pokhrel, Dinesh B (Journal of Pathology of Nepal, 2018)
Background: Tumours and tumour like lesions of skin have overlapping clinical presentation and sometimes pose a diagnostic difficulty on clinical ground alone. Histopathological examination although helpful to arrive at correct diagnosis, at times may be treacherous and may require ancillary tests such as Immunohistochemistry. Materials and Methods: The study was conducted at Department of Pathology of Tribhuvan University Teaching Hospital. It was a one year prospective study which enrolled 238 cases of skin biopsies after histopathological confirmation of tumours and tumour like lesions. The specimens were processed by standard method and Hematoxylin and Eosin stained sections were examined. Data entry and analysis was done by using SPSS 20 version. Results: Epidermal cyst was commonest lesion (11.8%). Among benign tumours squamous papilloma was most frequent while Pilomatricoma and Spiradenoma were most common adnexal tumour. Squamous cell carcinoma constituted 41.8% and was commonest malignant tumour followed by basal cell carcinoma (30.2%). Benign tumours were common in 11-30 years of age, malignant tumours in 61-80 years of age while tumour like lesions were common in 21-30 years of age. Conclusion: Squamous papilloma and squamous cell carcinoma was the most common benign and malignant tumour respectively. Benign adnexal tumours exceeded malignant one and were seen in third decade of life. Epidermal cyst was the commonest tumour like lesions followed by dermoid cysts.